2017
DOI: 10.2147/ijnrd.s131869
|View full text |Cite
|
Sign up to set email alerts
|

The role of novel biomarkers in childhood idiopathic nephrotic syndrome: a narrative review of published evidence

Abstract: Two histological subtypes of idiopathic nephrotic syndrome are commonly recognized in children, namely minimal change nephropathy and focal segmental glomerulosclerosis. Children with minimal change nephropathy (the majority of whom are steroid-sensitive) and focal segmental glomerulosclerosis (the majority of whom are steroid-resistant) require early identification in order to ensure appropriate therapeutic intervention and better outcome. Although renal biopsy and histology remain the ideal diagnostic steps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Several novel biomarkers have also been identified in the evaluation of childhood CKD: especially CKD secondary to idiopathic nephrotic syndrome and diabetic nephropathy (DN) [2,50].…”
Section: Chronic Kidney Disease (Ckd) and Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…Several novel biomarkers have also been identified in the evaluation of childhood CKD: especially CKD secondary to idiopathic nephrotic syndrome and diabetic nephropathy (DN) [2,50].…”
Section: Chronic Kidney Disease (Ckd) and Biomarkersmentioning
confidence: 99%
“…The use of biomarkers in childhood idiopathic nephrotic syndrome has been well documented [2]. It represents a non-invasive approach in diagnostic nephrology, as these markers can be used in the prediction and prognostic evaluation of the disease, as well as in differentiating steroid-resistant nephrotic syndrome (SRNS) from steroid-sensitive nephrotic syndrome (SSNS).…”
Section: Biomarkers Of Idiopathic Nephrotic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…The cause of CPNS is not known in most cases. However, recent studies suggested that genetic factors, such as single nucleotide polymorphisms (SNPs), might contribute to the susceptibility of CPNS …”
Section: Introductionmentioning
confidence: 99%
“…The idiopathic type of FSGS is diagnosed after ruling out these mentioned causes; otherwise, it is diagnosed as secondary type 2 . Clinically, FSGS is often associated with nephrotic syndrome, which is characterized by proteinuria of > 1 g/ m 2 /24 h, hypoalbuminemia, generalized edema, and hyperlipidemia 5,6 . The other clinical presentations of FSGS are hypertension, microscopic hematuria, renal failure, and serum creatinine increment 7 .…”
Section: Introductionmentioning
confidence: 99%